2015
DOI: 10.1589/jpts.27.3245
|View full text |Cite
|
Sign up to set email alerts
|

An efficacy study on improving balance and gait in subacute stroke patients by balance training with additional motor imagery: a pilot study

Abstract: [Purpose] The few studies conducted on subacute stroke patients have focused only on gait function improvement. This study therefore aimed to confirm the effect of balance training with additional motor imagery on balance and gait improvement in subacute stroke patients. [Subjects and Methods] Participants were divided into an experimental or control group. The experimental group received balance training for 20 minutes/day with mental imagery for 10 minutes/day, three days/week, for four weeks. The control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 22 publications
0
17
0
8
Order By: Relevance
“…Our data confirmed that MIP might significantly enhance motor performance of a complex postural task. Previous behavioral studies focusing on the impact of MIP on postural control (usually incorporated in a locomotor task) used longitudinal assessments and involved several training sessions per week, within a span of at least 2 weeks 11 , 33 37 . Interestingly, the present study extends these findings and provides evidence that a small amount of MIP without any physical practice might be sufficient to impact the postural control.…”
Section: Discussionmentioning
confidence: 99%
“…Our data confirmed that MIP might significantly enhance motor performance of a complex postural task. Previous behavioral studies focusing on the impact of MIP on postural control (usually incorporated in a locomotor task) used longitudinal assessments and involved several training sessions per week, within a span of at least 2 weeks 11 , 33 37 . Interestingly, the present study extends these findings and provides evidence that a small amount of MIP without any physical practice might be sufficient to impact the postural control.…”
Section: Discussionmentioning
confidence: 99%
“…After three weeks, gait speed and four of the six muscle groups tested were significantly faster and stronger, respectively, in patients in the experimental group as compared to the control group. Further, a pilot study of 20 subacute stroke patients investigated MI in conjunction with conventional balance training [ 81 ]. The experimental group performed balance training for 20 minutes/day and an additional 10 minutes/day of MI training for three days/week for four weeks.…”
Section: For Post-stroke Rehabilitationmentioning
confidence: 99%
“…The results of the study in the control group, where only physical training was carried out, and in the research group, where for physical training, the research group, where physical training took place. Test measures used for Berg Balance Scale, Timed Up and Go test, technical test, as well as Four Square Step test [16].…”
Section: Ndt Bobath (Neurodevelopmental Treatment)mentioning
confidence: 99%